Serious games: Harun Farocki og den militære æstetik - Engberg-Pedersen, Anders (Passage - Tidsskrift for litteratur og kritik, 2018)
Anders Engberg-Pedersen: “Serious games. Harun Farocki and Military Aesthetics” This article charts the emergence of a military-aesthetic regime in the twenty-first century. It shows how the US military has co-opted and militarized the field of aesthetics through the development of virtual worlds that train, prepare, and process military engagements. Using the German artist Harun Farocki’s installation Serious Games as a prism for this development, the essay charts the collaborations between military institutions, academics, and the creative industries. The key question is: what happens to the notion of “war experience” in the age of immersive virtual reality technologies? To find plausible answers, the article situates military aesthetics along a historical axis with the emergence of the modern wargame around 1800, and along a theoretical axis by drawing on key thinkers in philosophical aesthetics (Baumgarten, Dewey, Rancière).